Performance of Microscopy for the Diagnosis of Malaria and Human African Trypanosomiasis by Diagnostic Laboratories in the Democratic Republic of the Congo: Results of a Nation-Wide External Quality Assessment. - Pierre Mukadi; Veerle Lejon; Barbara Barbé; Philippe Gillet; Christophe Nyembo; Albert Lukuka; Joris Likwela; Crispin Lumbala; Justin Mbaruku; Wim Vander Veken; Dieudonné Mumba; Pascal Lutumba; et al. (PLoS ONE, 2016)
The present External Quality Assessment (EQA) assessed microscopy of blood parasites among diagnostic laboratories in the Democratic Republic of the Congo. The EQA addressed 445 participants in 10/11 provinces (October 2013-April 2014). Participants were sent a panel of five slides and asked to return a routinely stained slide which was assessed for quality of preparation and staining. Response rate was 89.9% (400/445). For slide 1 (no parasites), 30.6% participants reported malaria, mostly Plasmodium falciparum. Only 11.0% participants reported slide 2 (Plasmodium malariae) correctly, 71.0% reported "malaria" or "Plasmodium falciparum" (considered acceptable). Slide 3 contained Plasmodium falciparum (109/μl) and Trypanosoma brucei brucei trypomastigotes: they were each reported by 32.5% and 16.5% participants respectively, 6.0% reported both. Slide 4 (Trypanosoma) was recognised by 44.9% participants. Slide 5 (Plasmodium ovale) was correctly reported by 6.2% participants, another 68.8% replied "malaria" or "Plasmodium falciparum" (considered acceptable). Only 13.6% of routine slides returned were correctly prepared and stained. The proportion of correct/acceptable scores for at least 4/5 slides was higher among EQA-experienced participants compared to first time participants (40.9% versus 22.4%, p = 0.001) and higher among those being trained < 2 years ago compared to those who were not (42.9% versus 26.3%, p = 0.01). Among diagnostic laboratories in Democratic Republic of the Congo, performance of blood parasite microscopy including non-falciparum species and Trypanosoma was poor. Recent training and previous EQA participation were associated with a better performance.